A modified pearlite microstructure to overcome the strength-plasticity trade-off of heavily drawn pearlitic wire. (1st January 2022) - Zhou, Lichu; Fang, Feng; Kumagai, Masayoshi; Pickering, Ed; Zhang, Xiaodan
Abstract: It has long been established that drawn pearlitic steel wires can achieve ultra-high strengths; however, this is usually achieved to the detriment of tensile and torsional ductility. Here, we employed a modified microstructure to overcome these trade-offs through a process involving simple multiple drawing and annealing steps. In this microstructure, the conventional pearlitic cementite plates are replaced by cementite nano-particles bridged by grain boundaries enriched with substitutional elements. After being subject to this modified processing route, 0.92%C steel wires were found to exhibit 2300 MPa tensile strength, 6.4% uniform elongation and 0.73 uniform torsion strain. The wires processed by the new route had higher ultimate strength than wires prepared by the traditional process to the same strain, but with much superior tensile and torsional ductility – indeed they match the ductility of strain-free pearlitic steel rod. Graphical abstract: Image, graphical abstract